Metode Analitycal Hierarchy Process Untuk Pemilihan Walikota Dan Wakil Walikota - EVAN ROSISKA (JURNAL ILMU PENGETAHUAN & SISTEM INFORMASI (JIPSI), 2018)
ABSTRACT In this study the authors conducted a study on the selection of Mayor and Deputy Mayor of the Sungai Penuh of using the Analytical Hierarchy Process (AHP), the election is required selection criteria and alternatives, as well as calculating the weight of the survey questionnaire to the respondent on the Sungai Penuh. After that, there should be consistency test to test the validity of the results obtained, and establish an alternative with the greatest weight as an option. Based on the analysis results for mayor and vice mayor of using the AHP, a decision hierarchy can be made from the very top level is the goal, namely to find the highest priority for the Mayor and Deputy Mayor to be elected Sungai Penuh. Then factor in choosing an alternative criterion of Mayor and Deputy Mayor, namely: the vision and mission, education, the bearer party, organization, and employment history. Based on the analysis performed using the AHP method, obtained the percentage of priority criteria for selecting the mayor and deputy mayor from highest to lowest are: Vision and Mission with a value of 24.9% and 24.3% to the value of education, organization with a value of 22, 5%, with the bearer of the Party 18.8%, and the recent history of work with a value of 9.5%. Key words: Decision, AHP, the Mayor and Deputy Mayor, Criteria, Alternatives.